PERCEIVED INSUFFICIENT MILK (PIM) AMONG MOTHERS OF 0-6 MONTHS INFANTS IN CIPAYUNG HEALTH CENTRE, DEPOK INDONESIA: A QUALITATIVE STUDY - Stella Maris Bakara; Sandra Fikawati (Proceedings of the International Conference on Applied Science and Health, 2018)
Background: Exclusive breastfeeding is breast milk given to infant since their birth to the age of 6 (six) months, without adding and/or replacing with other foods or beverages (except medicines, vitamins, and minerals). One of the factors that affect the exclusive breastfeeding was the perceptions of insufficient milk. Milk insufficiency is considered to happen when the mother stops breastfeeding exclusively with some reasons such as no breast milk, low milk supply, or insufficient milk. This research was to examine more deeply the perception of insufficient milk and factor influencing it. Methods: This was a qualitative study that used a primary data of study "Intervention of Breastfeeding Enhancement and Weaning Food in the Implementation of the First-1000-Days-of-Life Program". Informants selected through who has been intervened research by PKGK. Triangulation of data sources was a midwife, informants’ husbands, documents of mother and child health books (MCH) and secondary data from PKGK research. Results: Based on the result from the interview: a) there was found a tendency of knowledge increase on mothers receiving treatment. b) Mostly, the lactation guidance was given without supporting device. c) Mother perception about their will gained weight if giving the sufficient milk has not been in line with Body Mass Index (BMI) before pregnancy. d). Family support towards mothers breastfeeding has not been provided optimally. e) Early breast-feeding (EBF) was not complete in accordance with the standard. Conclusions: Mothers who had not received treatment were having lack of knowledge on exclusive breastfeeding. Implementation of EBF was not in line with the procedure. The role of a delivery helper on EBF is vital in order to make the implementation of the EBF carried out according to the procedure.